Improving Reading Skills Through Our "Kacakarya" Reading We Create Using a Montessori Approach - Nida Hoerunisa; Ahmad Fajar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The low reading abilities and skills of children have become an important reason to improve reading literacy among children in Kampung Gunung Bakti Rt 04, Desa Cihanjawar. The low level of education in the community, dominated by graduates of elementary school, is one of the factors causing a lack of awareness among parents in providing guidance to their children about the importance of developing reading habits from an early age. Reading can be a support for achieving educational goals in Indonesia and should be made a routine daily activity. Reading literacy is a process that involves the ability to read, comprehend and analyze various information obtained to solve problems that arise in daily life with the aim of improving the quality of life. This community service aims to improve the reading literacy abilities and skills, with a focus on improving children's reading abilities. The service used a collaborative Participatory Action Research (PAR) design. The author collaborated with the managers of MI Al-Barokah and Rumah Belajar Muttaqin located in Kampung Gunung Bakti Rt 04, Desa Cihanjawar. The research results showed a 60% increase in children's reading abilities. The improvement of reading literacy skills requires support from all parties to further increase the success.